Noradrenergic modulation of rhythmic neural activity shapes selective attention. Issue 1 (January 2022) - Dahl, Martin J.; Mather, Mara; Werkle-Bergner, Markus
Abstract : During moments involving selective attention, the thalamus orchestrates the preferential processing of prioritized information by coordinating rhythmic neural activity within a distributed frontoparietal network. The timed release of neuromodulators from subcortical structures dynamically sculpts neural synchronization in thalamocortical networks to meet current attentional demands. In particular, noradrenaline modulates the balance of cortical excitation and inhibition, as reflected by thalamocortical alpha synchronization (~8–12 Hz). These neuromodulatory adjustments facilitate the selective processing of prioritized information. Thus, by disrupting effective rhythmic coordination in attention networks, age-related locus coeruleus (LC) degeneration can impair higher levels of neural processing. In sum, findings across different levels of analysis and modalities shed light on how the noradrenergic modulation of neural synchronization helps to shape selective attention. Highlights: Neural synchronization, particularly in the alpha frequency band (~8–12 Hz), supports routing prioritized information through thalamocortical attention networks. The noradrenergic locus coeruleus (LC) has long been regarded as the nexus of a global arousal system, unable to innervate attention-relevant specific cortical networks. Recent evidence reveals a more specialized neuromodulatory system, which biases processing in thalamocortical circuits according to attentional demands. Transient LC activations facilitate the selective processing of relevant information by flexibly adjusting local cortical excitability via thalamocortical alpha synchronization. However, with advancing age, the LC harbors toxins and Alzheimer's-related tau precursors, making it susceptible to neurodegeneration, which may disrupt synchronization in the aging brain.